Development of Physical Education Learning Assessment Instruments - Jamil, Zaky Ardhan; Masrun, Masrun; Pranoto, Nuridin Widya; Firdaus, Kamal; Andika, Heru; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to develop a valid, reliable and effective physical education learning assessment instrument for use in physical education learning. This instrument is designed to measure various aspects such as cognitive, apactive and psychomotor of students comprehensively. The method used in this study is Research and Development (R&D), which involves 3 experts, consisting of physical education experts, measurement test experts and language experts, for the field trial group involving 20 small groups and 30 large groups, after the data is obtained and analyzed using statistical analysis with the SPSS application with the r correlation method. The results of the study showed that the resulting instrument had a "very good" level of validity and reliability. Physical education teachers assessed that the instrument created helped in conducting objective assessments. But it still requires further development such as combining with digital technology to make assessment data more efficient and accurate.